SELF-COMPASSION DAN SELF-EFFICACY DENGAN FLOURISHING PADA MAHASISWA TINGKAT AKHIR - Nisa Oktafiani, Khairun; Ekasari, Agustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
This research aims to determine the relationship between selfcompassion, self-efficacy and flourishing in final year students, and flourishing in final year students. This research is a correlational quantitative research. The subjects of this research were students the total sample was 263 students taken using purposive sampling. The measurement instrument uses a psychological scale consisting of a self-compassion, a self-efficacy, and a flourishing using a Likert scale. Reliability uses the Cronbach's Apha formula for the self-compassion scale and the value obtained is ralpha = 0.906, the self-efficacy scale ralpha = 0.913, the flourishing scale ralpha = 0.928. The Spearman rank correlation test of self-compassion and flourishing a correlation of 0.400, so there is a significant relationship between self-compassion and flourishing in the medium category. The Spearman rank correlation test of academic self-efficacy and flourishing obtained a correlation coefficient value of 0.283, so there is a significant relationship between self-efficacy with flourishing is in the low category. The multiple regression test of self-compassion and self-efficacy with flourishing shows that the probability level results show a value of sig (p) = 0.000 (p < 0.05), so it can be concluded that there is a relationship between selfcompassion, self-efficacy and flourishing of students class of 2017 who are writing their theses. The correlation between the variables is large and flourishing is 0.466. The coefficient of determination (R2) = 0.217 which means that the variable self-compassion, selfefficacy contributes to the influence on flourishing by 21.7% and 78.3% by other variables.